Three-Dimensional Study of Alzheimer’s Disease Hallmarks Using the iDISCO Clearing Method - Thomas Liebmann; Nicolas Renier; Karima Bettayeb; Paul Greengard; Marc Tessier‐Lavigne; Marc Flajolet (2016)
Amyloidosis is a major problem in over one hundred diseases, including Alzheimer's disease (AD). Using the iDISCO visualization method involving targeted molecular labeling, tissue clearing, and light-sheet microscopy, we studied plaque formation in the intact AD mouse brain at up to 27 months of age. We visualized amyloid plaques in 3D together with tau, microglia, and vasculature. Volume imaging coupled to automated detection and mapping enables precise and fast quantification of plaques within the entire intact mouse brain. The present methodology is also applicable to analysis of frozen human brain samples without specialized preservation. Remarkably, amyloid plaques in human brain tissues showed greater 3D complexity and surprisingly large three-dimensional amyloid patterns, or TAPs. The ability to visualize amyloid in 3D, especially in the context of their micro-environment, and the discovery of large TAPs may have important scientific and medical implications.